INVESTIGATION OF DURABILITY OF CONCRETE EXPOSED TO NATURAL WEATHERING. REPORT NO. 5. SUMMARY OF RESULTS 1936-1953. - ARMY ENGINEER WATERWAYS EXPERIMENT STATION VICKSBURG MISS (1954)
The establishment of exposure stations, and the conduct of programs of investigations relative to the durability of concrete exposed to natural weathering have been authorized from time to time by the Office, Chief of Engineers. The initial installation of concrete specimens at an exposure station was made at Treat Island, Maine, in 1936 by the Concrete Laboratory of the Passamaquoddy Tidal PowerProject. In 1939 the Office, Chief of Engineers, authorized the Central Concrete Laboratory, North Atlantic Division, to develop data relative to the durability of concrete exposed to severe weathering. Under this authorization specimens were prepared and installed at exposure stations in Maine, Florida, and New York. In 1946 the Office, Chief of Engineers, directed the Concrete Research Division of the Waterways Experiment Station (successor to the Central Concrete Laboratory) to continue the work in connection with these exposure stations. Results of these various investigations have been reported from time to time. Because many of these reports are out of print, this report includes a summary of all of the investigations, with a more detailed description of those that are continuing. (Author)